Effect of 3, 2-Drug Combinations of Antihypertensive Therapies on Blood Pressure Variability in Black African Patients: Secondary Analyses of the CREOLE Trial. Issue 11 (2nd September 2022) - Ojji, Dike B.; Cornelius, Victoria; Partington, Giles; Francis, Veronica; Pandie, Shahiemah; Smythe, Wynand; Hickman, Nicky; Barasa, Felix; Damasceno, Albertino; Dzudie, Anastase; Jones, Erika; Ingabire, Prossie Merab; et al.
Abstract : Background: The effect of 3 commonly recommended combinations of anti-hypertensive agents—amlodipine plus hydrochlorothiazide (calcium channel blocker [CCB]+thiazide), amlodipine plus perindopril (CCB+ACE [angiotensin-converting enzyme]-inhibitor), and perindopril plus hydrochlorothiazide (ACE-inhibitor+thiazide) on blood pressure variability (V) are unknown. Methods: We calculated the blood pressure variability (BPV) in 405 patients (130, 146, and 129 randomized to ACE-inhibitor+thiazide, CCB+thiazide, and CCB+ACE-inhibitor, respectively) who underwent ambulatory blood pressure monitoring after 6 months of treatment in the Comparisons of Three Combinations Therapies in Lowering Blood Pressure in Black Africans trial (CREOLE) of Black African patients. BPV was calculated using the SD of 30-minute interval values for 24-hour ambulatory BPs and for confirmation using the coefficient of variation. Linear mixed model regression was used to calculate mean differences in BPV between treatment arms. Within-clinic BPV was also calculated from the mean SD and coefficient of variation of 3 readings at clinic visits. Results: Baseline distributions of age, sex, and blood pressure parameters were similar across treatment groups. Participants were predominately male (62.2%) with mean age 50.4 years. Those taking CCB+thiazide had significantly reduced ambulatory systolic and diastolic BPV compared with those taking ACE-inhibitor+thiazide. The CCB+thiazide and CCB+ACE-inhibitor groups showed similar BPV. Similar patterns of BPV were apparent among groups using within-clinic blood pressures and when assessed by coefficient of variation. Conclusions: Compared with CCB-containing combinations, ACE-inhibitor plus thiazide was associated with higher levels, generally significant, of ambulatory and within-clinic systolic and diastolic BPV. These results supplement the differential ambulatory blood pressure–lowering effects of these therapies in the CREOLE trial.